Proteolytic Activation of the Essential Parasitophorous Vacuole Cysteine Protease SERA6 Accompanies Malaria Parasite Egress from Its Host Erythrocyte - Ruecker, Andrea (American Society for Biochemistry and Molecular Biology, 2012)
The malaria parasite replicates within an intraerythrocytic parasitophorous vacuole (PV). The PV and host cell membranes eventually rupture, releasing merozoites in a process called egress. Certain inhibitors of serine and cysteine proteases block egress, indicating a crucial role for proteases. The Plasmodium falciparum genome encodes nine serine-repeat antigens (SERAs), each of which contains a central domain homologous to the papain-like (clan CA, family C1) protease family. SERA5 and SERA6 are indispensable in blood-stage parasites, but the function of neither is known. Here we show that SERA6 localizes to the PV where it is precisely cleaved just prior to egress by an essential serine protease called PfSUB1. Mutations that replace the predicted catalytic Cys of SERA6, or that block SERA6 processing by PfSUB1, could not be stably introduced into the parasite genomic sera6 locus, indicating that SERA6 is an essential enzyme and that processing is important for its function. We demonstrate that cleavage of SERA6 by PfSUB1 converts it to an active cysteine protease. Our observations reveal a proteolytic activation step in the malarial PV that may be required for release of the parasite from its host erythrocyte.